Understanding alcohol-involved sexual aggression through the science of behavior change - Davis, Klelly Cue (Alcohol and sexual violence, 2023)
Sexual aggression remains a significant public health concern, and alcohol intoxication is a key contributor to its occurrence. Despite its prevalence and harmful consequences, interventions addressing the specific mechanisms underlying alcohol-involved sexual aggression are lacking. In the present chapter, we argue that an experimental medicine approach to identifying, measuring, and targeting postulated mechanisms contributing to sexual aggression would enhance these intervention efforts. To that end, we review the extant research on sexually aggressive behavior, focusing on key cognitive, physiological, and emotional mechanisms. Within each of these areas, we examine the research regarding alcohol’s relationship to the mechanism as well as the existence and effectiveness of interventions targeting said mechanisms. Finally, we present as an exemplar a study that used an experimental medicine approach to investigate the utility of targeting emotion regulation as a mechanism underlying alcohol-involved sexual aggression, with additional suggestions for other novel investigations utilizing this paradigm. We conclude that by capitalizing on both new and established rigorous experimental methods, researchers can identify and target the mechanisms of behavior change underlying alcohol-involved sexual aggression, thereby increasing the effectiveness of sexual aggression prevention and intervention programs.